2011
DOI: 10.1073/pnas.1105673108
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant femtosecond laser vaporization of aqueous protein preserves folded structure

Abstract: Femtosecond laser vaporization-based mass spectrometry can be used to measure protein conformation in vitro at atmospheric pressure. Cytochrome c and lysozyme are vaporized from the condensed phase into the gas phase intact when exposed to an intense (10 13 W∕cm 2 ), nonresonant (800 nm), ultrafast (75 fs) laser pulse. Electrospray postionization time-of-flight mass spectrometry reveals that the vaporized protein maintains the solution-phase conformation through measurement of the charge-state distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 64 publications
2
56
0
Order By: Relevance
“…The major advance claimed is that proteins vaporized by a femtosecond laser can retain a folded structure during this process. This observation is rationalized since the energy from the laser is deposited much faster than that required to produce unfolding or reorganization of protein structure [3]. The authors use the charge state signature of the protein to conclude that the folded conformation is retained during, and immediately after, laser desorption.…”
Section: Can Charge State Signatures Be Used As Evidence Of Folding?mentioning
confidence: 99%
See 2 more Smart Citations
“…The major advance claimed is that proteins vaporized by a femtosecond laser can retain a folded structure during this process. This observation is rationalized since the energy from the laser is deposited much faster than that required to produce unfolding or reorganization of protein structure [3]. The authors use the charge state signature of the protein to conclude that the folded conformation is retained during, and immediately after, laser desorption.…”
Section: Can Charge State Signatures Be Used As Evidence Of Folding?mentioning
confidence: 99%
“…Levis and colleagues have described a femtosecond laser vaporization method in which folded protein structure is thought to be conserved [3]. In these experiments, a protein-containing solution, placed on a steel sample plate, is vaporized by a laser pulse.…”
Section: Can Charge State Signatures Be Used As Evidence Of Folding?mentioning
confidence: 99%
See 1 more Smart Citation
“…2 arises because we defined gas phase as the transfer of protein into the atmosphere for subsequent entrainment into the electrospray ionization plume (1), and Breuker et al (2) define gas phase as the protein state after complete desolvation in vacuum. Our work showed that the measured charge state distribution detected in vacuum was a signature of the condensed phase structure (1).…”
mentioning
confidence: 90%
“…We showed that the signatures for laser-vaporized protein revealed the anticipated charge state distribution, where conventional electrospray ionization (ESI) measurement promoted unfolding well before the vacuum state was obtained (1). Conventional ESI can distort protein structure determination because of both equilibrium ESI solvent effects and ionic effects in the Taylor cone.…”
mentioning
confidence: 99%